Economics, Law and Humanities: Homo-what? - Silvestri, Paolo (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
This introduction explains the reasons behind this Special issue and discuss the organization and content of it. The difficulty of a genuine dialogue and understanding between economics, law and humanities, seems to be due not only to the fragmentation of reflections on man, but to a real ‘conflict of anthropologies’. What kind of conceptions of man and human values are presupposed by and / or privileged by economics, law, economic approaches to law and social sciences? How and when do these conceptions come into conflict within and between disciplines? How do these conceptions of man and his values influence the conceptions of economics, law and institutions, and vice versa, how do these last conceptions influence the former? What are the normative, regulatory and practical implications of assuming an anthropological and / or axiological perspective instead of another? This Special issue aims at exploring the possibility of finding a common ground for discussion between economics, law and humanities, through the analysis and comparison of both the conceptions of man, human action and values assumed by economics, law and humanities, and their normative implications. The contributions to this Special issue and its organization are outlined at the end of this introduction. Keywords: Economics; Law; Humanities; Conceptions of man; Conflict of anthropologies Index: 1. The premise: a ‘conflict of anthropologies’? – 2 This Special Issue – References